2019
DOI: 10.1158/2326-6066.cir-18-0337
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Lymphatic Function Regulates Tumor Inflammatory and Immunosuppressive Microenvironments

Abstract: Proliferation of aberrant, dysfunctional lymphatic vessels around solid tumors is a common histologic finding. Studies have shown that abnormalities in lymphatic function result in accumulation of inflammatory cells with an immunosuppressive profile. We tested the hypothesis that dysfunctional lymphatic vessels surrounding solid tumor regulate changes in the tumor microenvironment and tumor-specific immune responses. Using subcutaneously implanted mouse melanoma and breast cancer tumors in a lymphatic endothel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 55 publications
(60 reference statements)
1
29
0
Order By: Relevance
“…A recent experimental study showed that mice with ablated lymphatics exhibited reduced intra-tumoral accumulation of cytotoxic T cells and increased tumor PD-L1 expression, causing rapid tumor growth. Additionally, impaired function of the peritumoral lymphatic vessels resulted in decreased migration of dendritic cells to draining SNs compared with normal flank skin-draining lymph nodes [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent experimental study showed that mice with ablated lymphatics exhibited reduced intra-tumoral accumulation of cytotoxic T cells and increased tumor PD-L1 expression, causing rapid tumor growth. Additionally, impaired function of the peritumoral lymphatic vessels resulted in decreased migration of dendritic cells to draining SNs compared with normal flank skin-draining lymph nodes [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, before cancer cells metastasize through these peritumoral lymphatics, tumor antigens (tAgs) and mature, activated dendritic cells presenting tAgs migrate through the peritumoral lymphatics to regional LNs to set up anti-tumor immune responses (Figure 1). Indeed, lymphangiogenesis and drainage to regional LNs may improve anti-tumor immune responses, as recently demonstrated by enhanced melanoma and breast cancer growth rates in preclinical models in which regional draining lymphatics were ablated [53].…”
Section: The Effects Of Metastasis and Cancer Progression On Lymphatimentioning
confidence: 92%
“…Furthermore, in cancer, LVs transport tumor cells to the lymph nodes, triggering metastasis 22,23 . It is also known that tumor LVs induce tumor immune escape and evasion 24,25 . All of these examples show how the lymphatic vascular system is largely involved and implicated in major human diseases.…”
Section: Introductionmentioning
confidence: 99%